Antibiofilm activity of aminopropanol derivatives against Pseudomonas aeruginosa - D. M. Dudikova; Z. S. Suvorova; V. V. Nedashkivska; A. O. Sharova; M. L. Dronova; N. O. Vrynchanu (The State Expert Center of the Ministry of Health of Ukraine, 2018)
Bacterial biofilm, particularly formed by Pseudomonas aeruginosa, are a cause of severe chronic infectious diseases. Bacteria within a biofilm are phenotypically more resistant to antibiotics and the macroorganism immune system, making it an important virulence factor for many microbes. The aminopropanol derivatives with adamantyl (KVM-97) and N-alkylaryl radicals (KVM-194, KVM-204, KVM-261, and KVM-262) were used as study object. The aim of this study was to investigate the antibiofilm activity of compounds on biofilm formation and on mature biofilm of P. aeruginosa. The effects of the aminopropanol derivatives on the biofilm mass were evaluated by using crystal violet assay. Ciprofloxacin, meropenem, ceftazidime, gentamicin were used as reference substances. Reported results demonstrate that all compounds displayed antibiofilm activity at the tested concentrations. Remarkable reduction in biofilm formation of P. aeruginosa was found after treatment with KVM-97, KVM-261 and KVM-262 in high concentration (5× MIC), biofilm inhibition activity were 84.3%, 90.5% and 83.3% respectively. After a treatment with KVM-204 at 250 μg/ml (5× MIC) 76.6% of the preformed 24-hr biofilms were destroyed. Furthermore, compounds KVM-97, KVM-194, and KVM-261 in both concentrations showed potent antibiofilm activity against the P. aeruginosa, inhibition activity values being between 56.7 and 65.7%. All tested compounds in dose-dependent manner exhibited pronounced inhibition activity against mature 5-days P. аeruginosa biofilm. It was also observed that tested compounds show high antibiofilm activity in comparison to reference antimicrobials. The aminopropanol derivatives may provide templates for a new group of antimicrobial agents and potential future therapeutics for treating chronic infections.